Educational Technology: False Profit or Sacrificial Lamb? A Review of Policy, Research, and Practice. (October 2016) - Lawless, Kimberly A.
New technologies are providing opportunities to guide and enhance learning that were unimagined even a few years ago. The promise of technology to help turn the tide on the declining effectiveness of the U.S. educational system has led to a swell of policies: placing technologies in our schools, mandates to use these technologies, and funding research on technology-enabled learning environments. This article reviews the impact of these endeavors, focusing on what is known about the use of contemporary technologies (i.e., digital games, social media, Massively Open Online Courses [MOOCs], and augmented reality) as tools for learners. While not comprehensive, the aggregate findings offer a means to stimulate dialogue on how we can alter our conception of formal education in the United States, as well as additional research and policy implications to support instantiation of new conceptions.